2009
DOI: 10.1002/bem.20551
|View full text |Cite
|
Sign up to set email alerts
|

Static magnetic field exposure fails to affect the viability of different bacteria strains

Abstract: The viability of the microbes Saccharomyces cerevisiae, Bacillus circulans, Escherichia coli, Micrococcus luteus, Pseudomonas fluorescens, Salmonella enteritidis, Serratia marcescens, and Staphylococcus aureus was tested under static magnetic field exposure up to 24 h in either a homogeneous (159.2 +/- 13.4 mT) or three types of inhomogeneous static magnetic fields: (i) peak-to-peak magnetic flux density 476.7 +/- 0.1 mT with a lateral magnetic flux density gradient of 47.7 T/m, (ii) 12.0 +/- 0.1 mT with 1.2 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
(33 reference statements)
0
8
1
Order By: Relevance
“…Indeed, we observed a spectrum of answers to the same antimicrobial (coupled with the RMF), depending on which staphylococcal strain it was applied against. This phenomenon, of pivotal significance in the studies on MF impact on micro-organisms, is often neglected, i.e., only one reference strain as an example of a given species is analyzed [ 61 , 62 , 63 ]. This specific methodological approach requires a separate line of investigation if proper conclusions on the observed effects are to be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we observed a spectrum of answers to the same antimicrobial (coupled with the RMF), depending on which staphylococcal strain it was applied against. This phenomenon, of pivotal significance in the studies on MF impact on micro-organisms, is often neglected, i.e., only one reference strain as an example of a given species is analyzed [ 61 , 62 , 63 ]. This specific methodological approach requires a separate line of investigation if proper conclusions on the observed effects are to be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…SMF; 100 mT; exposure time 30, 60, 120, 240 min the MF exposure for 30 min had no effect on bacterial cell density; the longer MF exposure (120, 240 min) caused growth inhibition [28] SMF; 7-11 Hz; exposure time 220 min the MF had no effect on DNA damage; the MF had stimulating effect on cell growth [29] SMF; 5, 17 and 50 mT; exposure time 1, 2, 3 and 4 h the MF negatively influences the growth; the MF caused an increase in dehydrogenase activity and higher intracellular ATP concentrations [30] SMF; 10 mT; 50 Hz; exposure time 1h the MF had no effect on bacterial morphology [1] SMF; 2 mT; 50 Hz; exposure time 6, 16 h the MF caused a decrease in the cell growth [31] SMF; 5.2-6.1 T; exposure time 30 h the MF increased suppression of cell death; the MF stimulated growth [32] SMF; 50 Hz; 1 mT; exposure time 8 min, 2, 5 and 15 h the MF had no effect on cell viability regardless of exposure time [33] SMF; 5.2-6.1 T; exposure time 12 h the MF caused a suppressive effect on the cell death rate [34] SMF; 45-3500 mT; exposure time 60 min the MF caused a decrease in the number of CFU; the MF influenced on cell surface damage [35] SMF; 300 mT; exposure time 50 h the MF had no effect on the growth; the MF stimulated transposition activity [36] SMF; 2.7-10 mT; 50 Hz; exposure time 0-12 min the MF affected the bacteria E. coli; the MF was not bacteriostatic; the MF had no effect on the metabolism of the bacteria; the MF killed a part of bacteria exposed [37] SMF; 5, 10 and 13 T; exposure time 24 h the MF had no effect on mutation frequency in thymine synthesis genes [38] E. coli; S. aureus SMF; 10 mT; 50 Hz; exposure time < 30 min the MF caused a decrease in the cell viability; the MF caused a decrease in CFU [20] DCMF; 0.5-4 T; exposure time 30-120 min the MF had no influence on growth [21] SMF; 30-100 mT; exposure time 30 h the MF had no effect on growth [22] homogeneous SMF (400 mT); inhomogeneous SMF; (1.2-47.7 T); exposure time 10, 30, 50, 1440 min the MF had no effect on growth [39] MF; up to 10 mT; 50 Hz; exposure time up to 24 min the MF caused a decrease in optical densities of bacterial cultures [40] SMF (DCMF); 10 T; exposure time 5-60 min the MF altered the components and structure of nucleic acid, protein, and fatty acids [37] S. aureus SMF; 50-20.000 Gauss the MF had no effect on growth, when the field strength increased there were a slight growth inhibition EMF; 20 Hz; 5 mT; exposure time 24 h the MF had no effect on growth on gel-like medium; the MF caused a decrease in growth in fluid medium [4] AC -alternating current; ACMF -alternating current magnetic field; DC -direct current; DCMF -direct current magnetic field; EF -electric field; EMF -electromagn...…”
Section: E Colimentioning
confidence: 99%
“…In spite of this approach, the data presented in the literature on the subject in question are often conflicting, and the mechanisms of MF's biological activity are still not elucidated (Table 1). As an example, some authors reported the antibacterial effect of MFs [7,10,26,27], while others suggested a lack of any significant impact of MFs on microbial growth [12,28], biochemical activity [5], or bacterial adhesion [29]. In turn, other research teams demonstrated a stimulating effect of MFs on microbial cell growth and cell viability [30][31][32].…”
Section: Introductionmentioning
confidence: 99%